Propriedades de formação de massa de pão elaborado com incorporação de tegumento de soja e composto fibroso de mandioca em farinha de trigo de grão inteiro - Durante, Viviane Vaz Oleiro (2020)
Whole wheat flour (WWF) is growing in the market and consumer acceptance due to the consumer´s request for more nutritious foods. Therefore, the development of functional foods by the addition of functional ingredients in products in an interesting alternative. Consequently, the inclusion of several ingredients, simultaneously, is increasingly present in the products available. Although beneficial to health, the presence of those ingredients, especially fibers, in wheat flour interferes in the dough formation, changing the characteristics of bakery products. Based in this, these properties must be studied to understand the influence of fibers from different sources, in the quality of final products and so minimize it. Thus, the objective is to evaluate the dough-forming properties of whole wheat flour incorporated with soybean tegument (ST) and fibrous cassava compound (FCC). Through a factorial design 22 with two central point. WWF was partially replaced by soy tegument (2, 6,10%) and fibrous cassava compound (3, 6, 9%), and rheological and hydration properties evaluated by the response surface methodology and the baking performance by the statistical desirability test. The inclusion of fibers resulted in increased stability and water absorption from the flour and reduced breakdown at RVA. The free sulfhydryl content increased with the increase in the substitution of whole wheat flour and the samples remained thermally stable up to 200°C. The extension analysis also showed reduced values as the proportion of added fibers increased. The presence of fibers interfered the correct hydration of gluten proteins, affecting the kinetics and the solvent retention capacity. The changes caused by FCC in hydration properties and the baking performance are more intense than ST. The desirability test indicated the central point (9% FCC and 6% ST) as the best condition in the baking performance.